Ammonia emissions in tunnel-ventilated broiler houses - Lima,KAO (2011)
Gas production in broiler houses and their emissions are closely related to the microclimate established inside the house according to air temperature, humidity, and velocity. Therefore, the internal house environment is influenced by building typology and ventilation system. The objective of the present study was to evaluate ammonia emission rates in broiler houses equipped with different ventilation systems (negative or positive pressure) and litter conditions (new or built-up). The environment of six commercial broiler houses was evaluated internal and external NH3 concentrations. Ventilation rates were recorded to estimate ammonia emission rates. The efficiency of circulation and exhaust fans was assessed, and higher ventilation rates were determined in negative-pressure houses due to the higher flow of the fans. Houses with new litter increased ammonia emission rates along the rearing period, indicating the relationship between gas emissions, bird age and ventilation rates, and presented a typical curve of NH3 emission increase. Negative-pressure houses with built-up litter presented higher emission rates during the first rearing week due to the high NH3 concentration during the brooding period, when the ventilation rates required to maintain chick thermal comfort are low. Although the results of the present study indicate an advantage of the positive-pressure systems as to gas emissions, further research is needed reduce gas emissions in broiler houses with negative-pressure systems.